(untitled) (Journal of Dhaka National Medical College & Hospital, 2018)
Chronic inflammatory demyelinating polyneuropathy (CIDP) is characterized by symmetrical weakness, involving both proximal and distal muscles with sensory impairment. Muscle wasting is rarely pronounced in CIDP. When a patient present with CIDP and muscle wasting may mimicking with motor neuron disease like spinomuscular atrophy (SMA), Progressive muscular atrophy (PMA). It is very important to distinguish between CIDP and motor neuron disease (MND) by clinical, laboratory and histological feature because of different effective therapeutic strategies. Our patient 35 years old male presented with tingling, numbness and weakness in all four limbs. On examination there was muscle weakness and wasting more in the distal than the proximal. Electrophysiological investigation showed mixed sensory, motor demyelinating and axonal polyradiculoneuropathy and on Electromyogram (EMG)- fibrillation was absent, CSF examination there was albuminocytological dissociation. We established this case as a CIDP though it was mimicking with MND and treatment was started with steroid and other disease modifying drugs. J. Dhaka National Med. Coll. Hos. 2018; 24 (02): 50-53